Changes in Childhood Environments in Finland, 1987-2023: Family and Neighbourhood Inequalities - Sivosavi, Juho-Kusti (My University, 2026)
In this thesis we map out how the inequalities related to childhood environment have changed over the last four decades in Finland. The various changes that the society has faced potentially influence the inequalities in childhood environments. Most notably income inequality increased in the 1990s, socioeconomic neighbourhood segregation has increased dramatically in the 2000s, the urbanization process is still ongoing and total fertility rate has dropped in recent years. However, our understanding of how exactly these developments have influenced the distribution of where children grow up in form of childhood family’s household income, parental education, neighbourhood income or the family composition is lacking. Further, the second interesting question is how strongly spatially concentrated different disadvantages are, and how this has changed over time. The thesis focuses on mapping these changes from 1987 to 2023, using high-quality Finnish register data. We find that the socio-spatial polarisation in childhood environments has increased especially in urban areas. Income differences between neighbourhoods have widened and single parenthood, low parental education, foreign background and unemployment have become increasingly concentrated in the lower income level neighbourhoods. Having a family member with at least tertiary education has become heavily connected with growing up in a higher income level neighbourhood. Additionally, the vast majority of children now grow in these polarised urban environments but are more strongly distributed into the higher-income families. This thesis links to the more general international discussions on whether changes in intergenerational mobility are associated with changed childhood environments or societal environment of the children once they have grown up.
Keywords: neighbourhood inequality; childhood environments; residential segregation.